Perceptions of the Instructional Research Training Environment and Research Self-Efficacy - Missy Moore; John McCall; Todd Bolin; Austen Bingham (Teaching and Supervision in Counseling, 2024)
We examined counselor education and supervision (CES) doctoral students’ (n = 117) perceptions of their instructional RTE and research self-efficacy. Students had more positive perceptions of their instructional RTE and higher research self-efficacy when research courses were taught by counseling faculty. Additionally, the instructional RTE was predictive of research self-efficacy above and beyond intrapersonal, interpersonal, and experiential variables. Implications for counselor education programs are provided.
Keywords: research training environment; research self-efficacy; research pedagogy; counselor education.